Developing automated strategy of life cycle cost analysis (LCCA) with building information modeling (BIM) integration for building projects - Muhammad Altaf; Rabeea Jaffari; Wesam Salah Alalaoul; Muhammad Ali Musarat; Syed Ammad (Results in Engineering)
The construction industry plays a substantial role in the economic prosperity and growth of all other sectors in any country. To foster the economic sustainability of a construction project, it is crucial to evaluate all the associated current and future project costs. To address the current and future related costs to a project, life cycle cost analysis (LCCA) is the most sophisticated economic approach. However, traditionally, LCCA is performed manually, and thus, limited implementation is observed due to time-consuming and tedious steps. To address the issue, this current research attempts to automate the LCCA process and develop an advanced algorithm for LCCA with building information modelling (BIM) integration. Following the algorithm, an LCCA-BIM tool is developed using C# programming language that automates the extraction of bills of quantities and facilitates the incorporation of cost data associated with a project with the LCCA parameter to determine life cycle cost. A case study was performed that validated the effectiveness of the algorithm in performing LCCA for a project. Integrating LCCA with BIM streamlines and automates the economic evaluation process and offers a robust framework for future advancement in LCCA implementation. The application leads to enhanced decision-making and encourages sustainability in building projects by eradicating barriers to retrieving and automating the LCCA.